Preferensi Masyarakat dalam Mengunjungi Ruang Terbuka Publik - Adzhani, Safira; Kusuma, Hanson Endra (http://arl-faperta.ipb.ac.id/, 2025)
Public open spaces are essential for sustainable urban development, offering places for recreation, social interaction, and physical activities. These spaces, designed by local governments, often attract both local residents and tourists. However, many public open spaces fail to fully adhere to infrastructure regulations set by the Ministry of Public Works and Housing (PUPR), highlighting the need for improved planning and design. This study aims to explore community preferences for visiting urban public open spaces to provide insights for better design and management. A qualitative, exploratory approach using grounded theory was employed, with data collected through open-ended online questionnaires distributed via non-random sampling. The responses were analyzed using content analysis. The findings reveal three primary categories of preferences: conception, physical-spatial attributes, and activities. The conception category includes elements such as tranquility, familiarity, attractiveness, novelty, and enjoyment. Physical-spatial preferences focus on accessibility, safety, cleanliness, spaciousness, and the natural environment. Activities, the most significant category, include learning, playing, culinary experiences, sports, recreation, relaxation, and social interaction.Activities received the highest score (66 points), followed by physical-spatial attributes (57 points) and conception (30 points). These results underscore the importance of designing spaces that support diverse activities while maintaining accessibility, safety, and environmental appeal. Recommendations for policymakers and urban planners include enhancing facilities, ensuring cleanliness and safety, and promoting inclusivity. By aligning public open space design with community preferences, cities can create vibrant spaces that meet the needs of urban residents and improve their quality of life.